A critical policy analysis of 'Teach for Bangladesh': a travelling policy touches down. Issue 2 (3rd April 2018) - Adhikary, Rino Wiseman; Lingard, Bob
ABSTRACT: This paper provides a critical policy analysis and network ethnography of Teach for Bangladesh ( TfB ). We demonstrate that TfB is a localised version of a global teacher education policy – Teach for All/America (TfAll/A) . Santos, Boaventura De Sousa [2002. The Processes of Globalisation . Translated by Sheena Caldmell. Eurozine: Revista Crítica de Ciências Sociais and Eurozine, August, 1–48] has written about the ways some national policies travel globally. He calls these 'globalised localisms'. When they touch down and are taken up in another national context, he calls this a 'localised globalism'. We see TfB as a 'localised globalism'. This paper is focused on documenting and analysing the policy network that has enabled a globalised localism, TfAll/A, to be taken up as a localised globalism in Bangladesh through TfB . We see this as the emergence of network governance in a developing world primary schooling context. The analysis shows how pivotal to TfB is the boundary spanning networking of its founder, who connects the global to the local, the private to the public, and the provision of social services to philanthropy.